Problems Faced by Married Women with Epilepsy in Indian Scenario: A Hospital-Based Study - Sharma, Sunil Kumar; Sardana, Vijay; Maheshwari, Dilip; Bhushan, Bharat; Jain, Nishtha; Shringi, Prashant; Bhattiprolu, Rahi Kiran (International Journal of Epilepsy, 2018)
Background Epilepsy is still being considered as a social stigma especially in developing countries such as India. This study was conducted to analyze the problems faced by married women with epilepsy in various aspects of personal and social life.Objectives The main purpose of this article is to study the psychosocial problems, drug compliance, clinical course, attitude of in-laws, and effect of epilepsy on pregnancy and its outcome in married women with epilepsy in Indian scenario.Design, Materials, and Methods This is a prospective observational study including 100 patients. Questionnaire-based face-to-face interview of all the patients was conducted. Patients were divided into informed and concealed groups and various attributes and their significance were compared. Statistical analysis was performed using SPSS-20.0 and Microsoft Office Excel software.Results Out of 100 patients, a total of 58 (58%) patients had informed prior to marriage, while 42 (42%) concealed it. Attitude of husband was negative in 33% (14 out of 42) of concealed group and was statistically significant (p = 0.03). Statistically significant adverse marital outcome was observed in concealed group and Muslim community (p = 0.0001). Majority of the patients in both groups (86%) opined that it should be disclosed prior to marriage.Conclusion In a developing country such as India, epilepsy is still considered a social stigma that can manifest as felt or enacted stigma. Previous studies clearly indicate increasing awareness. Social stigma associated with epilepsy can only be eliminated with collaborative efforts of healthcare professional, government, and general public.
Keywords: married women with epilepsy; social stigma; marital outcome